(untitled) (Pulse, 2025)
The distribution pattern of ABO blood group and Rhesus-D type varies in different parts of the Bangladeshi population. This study was carried out to determine the frequency of ABO and RhD blood group among all the donors and patients both (OP and IP) attending Evercare Hospital Chattogram. Blood grouping has been conducted in the Department of Transfusion Medicine. Blood group reports of 7,226 donors and 14,866 inpatients (both OPD and IPD) were analyzed retrospectively, starting from April 2021 to March 2025. Blood grouping was performed by column agglutination technique using gel card and traditional hemagglutination technique using slide/tube test. Both forward and reverse typing was done to confirm ABO blood group, and Du test was performed to confirm RhD blood group when required. The most common ABO blood group was found to be O (36.8%) followed by B (30.7%), A (24.8%) and AB (7.8%). Regarding RhD type, RhD positive group was 96.6%, RhD negative 3.4% and Du positive 0.11% Pulse Vol.17, 2025 P: 19-22